Feminisme Eksistensialis dalam Cerpen Perempuan Yang Menikahi Tubuhnya Sendiri Karya M. Rifdhal Ais Annafis: Perspektif Simone De Beauvoir - Nora Erika Aulia; Agik Nur Efendi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The meaning of freedom for a woman does not only include equality in terms of work, opinion, or decision-making, but also the right to live free from patriarchal views, sexual violence, and subordination. Existentialist feminism presents as a critique of patriarchal domination and the labeling of the other or "other" against the position of women. This study aims to examine the existence of women in the short story "Women Who Married Their Own Bodies" by M Rifdal Ais Annafis using Simone De Beauvoir's existentialist feminism approach, while also exploring its potential as critical literacy material in future literary education. The method used in this study is a qualitative descriptive method with library study data collection techniques and reading and note-taking techniques. The data analysis technique uses content analysis with the stages of data reduction, data presentation, interpretation, and drawing conclusions. The results of the study show that the female characters in the short story experience social and family pressure, but try to resist through existential awareness and affirmation of their bodies and choices. The phenomenon of subordination against women is also found, revealed through the exposure of cases of murder and harassment of teenage girls. Thus, this research not only expands the study of existentialist feminism in literature, but also contributes to the development of literary education that is inclusive, reflective, and responsive to issues of gender equality in the current and future social context.